Mechanical Performance of Concrete Made with Recycled Aggregates from Concrete Pavements - Yancong Zhang; Lingling Gao; Wei Bian (Advances in Materials Science and Engineering)
This research aims at analysing the mechanical performance of concrete with recycled aggregates from concrete pavements. First, the characteristics of various natural and recycled aggregates used in the concrete were thoroughly analysed. The composition of the recycled aggregates was determined and several physical and chemical tests of the aggregates were performed. In order to evaluate the mechanical performance of recycled concrete, cube compressive strength and flexural tensile strength tests were performed. The effect of recycled aggregates on the strength of recycled concrete is related to the strength of recycled aggregates, the strength of natural aggregates, and the strength of old concrete. The strength of recycled concrete decreases with increasing water-cement ratio. However, due to the water absorption of the recycled aggregate, it has a certain inhibitory effect on the strength reduction. As the replacement rate of recycled aggregates increases, the optimal sand ratio decreases. The sand ratio is controlled between 32% and 38%, which is ideal for recycled concrete. With the increase of fly ash content, the 7 d strength of recycled concrete has decreased to some extent, but the 28 d strength has been slightly improved. In addition, for compressive strength and flexural tensile strength, the optimal content of fly ash is different.